Isolation of nuclear proteins from flax (Linum usitatissimum L.) seed coats for gene expression regulation studies - Renouard Sullivan; Cyrielle Corbin; Lopez Tatiana; Lamblin Frédéric; Lainé Eric; Hano Christophe (BMC Research Notes, 2012)
Abstract Background While seed biology is well characterized and numerous studies have focused on this subject over the past years, the regulation of seed coat development and metabolism is for the most part still non-elucidated. It is well known that the seed coat has an essential role in seed development and its features are associated with important agronomical traits. It also constitutes a rich source of valuable compounds such as pharmaceuticals. Most of the cell genetic material is contained in the nucleus; therefore nuclear proteins constitute a major actor for gene expression regulation. Isolation of nuclear proteins responsible for specific seed coat expression is an important prerequisite for understanding seed coat metabolism and development. The extraction of nuclear proteins may be problematic due to the presence of specific components that can interfere with the extraction process. The seed coat is a rich source of mucilage and phenolics, which are good examples of these hindering compounds. Findings In the present study, we propose an optimized nuclear protein extraction protocol able to provide nuclear proteins from flax seed coat without contaminants and sufficient yield and quality for their use in transcriptional gene expression regulation by gel shift experiments. Conclusions Routinely, around 250 μg of nuclear proteins per gram of fresh weight were extracted from immature flax seed coats. The isolation protocol described hereafter may serve as an effective tool for gene expression regulation and seed coat-focused proteomics studies.